Análisis y evolución histórica de los nombres de marcas de zapatillas deportivas. [Analysis and historical evolution of the names of sport footwear brands]. - José A. Martínez; Jorge Muñoz (Revista Internacional de Ciencias del Deporte, 2014)
The marketing literature considers that choosing the name of a brand is an important concern for executives, in order to build brand equity for a new product (Aaker, 1996). In a dynamic and growing industry such as sport footwear, this research achieved an analysis of the different types of brand names, with the aim to establish a description of the disparate forms of creating a brand name. In addition, this study showed the historical evolution of brand names, from the end of the XIX century to the current days. Through the analysis of 196 brand names coming from divergent countries, and after applying the content analysis method, results showed a complete picture about how to name a sport footwear brand. Moreover, findings indicated several significant changes along time, regarding the form of naming a brand, from the semantic, phonetic and morphologic viewpoint. Implications for the managing of this type of products were finally discussed.